Impact of network security on spech quality - Parada, Saul (2011)
This dissertation is about the impact of secure network environments on speech quality of IP Telephony. Results of the analysis of voice over different unsecure and secure communication links, such as IPsec and TLS, are presented. The use of secure network environments can affect speech quality. There is also a performance comparison of different cipher algorithms and a description on how the used security mechanisms influence the final MOS and R-factor variables. The presented results are based on numerous experiments which have been performed on a real IP-based network.